X‐ray microtomography reveals a lattice‐like network within aortic elastic lamellae. Issue 10 (2nd September 2021) - Ben Zemzem, Aïcha; Genevaux, Aline; Wahart, Amandine; Bodey, Andrew J.; Blaise, Sébastien; Romier‐Crouzet, Béatrice; Jonquet, Jessica; Bour, Camille; Cogranne, Rémi; Beauseroy, Pierre; Dauchez, Manuel; Sherratt, Michael J.; et al.
Abstract: The arterial wall consists of three concentric layers: intima, media, and adventitia. Beyond their resident cells, these layers are characterized by an extracellular matrix (ECM), which provides both biochemical and mechanical support. Elastin, the major component of arterial ECM, is present in the medial layer and organized in concentric elastic lamellae that confer resilience to the wall. We explored the arterial wall structures from C57Bl6 (control), db / db (diabetic), and ApoE −/− (atherogenic) mice aged 3 months using synchrotron X‐ray computed microtomography on fixed and unstained tissues with a large image field (8 mm 3 ). This approach combined a good resolution (0.83 µm/voxel), large 3D imaging field. and an excellent signal to noise ratio conferred by phase‐contrast imaging. We determined from 2D virtual slices that the thickness of intramural ECM structures was comparable between strains but automated image analysis of the 3D arterial volumes revealed a lattice‐like network within concentric elastic lamellae. We hypothesize that this network could play a role in arterial mechanics. This work demonstrates that phase‐contrast synchrotron X‐ray computed microtomography is a powerful technique which to characterize unstained soft tissues.